Кратність на рівні макроструктури художнього тексту - Рожко, С.В. (Культура народов Причерноморья, 2013)
У статті розглядаються художній час, що є освідомленням статистичного образу рухомої відносної темпоральної структури як категорії тексту . В статье рассматривается художественное время, что является осознанием статистического образа движимой относительной темпоральной структуры как категории текста. In the article considered considered artistic time which is the awareness of statistical image of movable relative temporal structure, as a category of text. organization of composition with separate types, or components, definite kind of activity which activated due to the nature of communicative act. Text Functional text category – it`s properties, which includes the system of the category of temporality imagery and so on represent us the link between the text and language system. The system generates a multiplicity of text category macrostructure special type. Meaning of the multiplicity of macrostructure notes the existence of verbal complex, which in general have a lot of akts similar to the semantics of the actual delivery of the grammatical category of multiplicity of verbal action. The definition of multiplicity at the level of the macrostructure of a literary text as a whole corresponds to its traditional explanation in function grammar, although attention focuses on the actualization of the internal semantics of the multiplicity of verbal units.